LEGAL SPEECH ACTS IN A COGNITIVE LINGUISTIC PERSPECTIVE – FOCUS ON MODALITY - WITCZAK-PLISIECKA, Iwona (Comparative Legilinguistics, 2009)
The paper involves three main fields of linguistic analysis: the pragmatic theory of speech acts, cognitive linguistics and legal language. Its main aim is to demonstrate the relevance of the cognitive framework to the analysis of speech acts and especially the deontic use of the modal verb shall in the legal context. The focus is on the use of the modal, which is mainly used to impose obligations or to confer rights. Thus, its meaning seems to be in most cases a combination of both assertive and directive illocutionary forces when approached from a pragmatic perspective, and a combination of deonticity with futurity and prediction in traditional grammar terminology. The discussion is illustrated with a variety of examples retrieved from a corpus of legal documents drafted in English and translated into Polish. It is argued that the meaning of most instances of shall in the legal domain, due to its context-sensitivity, can be best accounted for in terms of a cognitive blend, which integrates various aspects of its meaning. These aspects are believed to be inherently vague and possibly an instance of ongoing processes of grammaticalisation, which can only be grasped with reference to the context of a particular expression, thus pragmatic in nature.